Exercise interventions to prevent hamstring injuries in athletes: A systematic review and meta-analysis. - Vatovec, R.; Kozinc, Z.; Sarabon, N. (European Journal of Sport Science, 2020)
The aim of this meta-analysis was to assess the effectiveness of exercise-based interventions for prevention of hamstring injuries in sport. PubMed, Cochrane Central Register of Controlled Trials, Web of Science, ResearchGate, CINAHL, PEDro, ScienceDirect and Google Scholar databases were searched for randomized controlled trials and prospective cohort studies exploring the effects of exercise interventions on hamstring injury incidence. Subgroup analyses were performed to determine effects of several independent variables related to the interventions. Altogether, 17 studies were included. Exercise interventions decreased hamstring injury risk (RR = 0.49; 95%CI = 0.40-0.59; p < 0.001). There were similar effects found for interventions performed =2 times per week (RR = 0.35; 95%CI = 0.15-0.82;) and the interventions performed >2 times per week (RR = 0.44; 95%CI = 0.31-0.61). Similarly, there were similar effects found for the interventions with progressive increase in load (RR = 0.53; 95%CI = 0.37-0.74) and the interventions with constant loads (RR = 0.46; 95%CI = 0.36-0.58). Other subgroup analyses (intervention supervision, sport type, inclusion of Nordic hamstring exercise and type of the trial) also showed no indications on specific characteristics of the interventions, that increase the preventive effects. Our findings showed that hamstring injury incidence can be decreased with exercise-based interventions, and that weekly frequency and load progression are not among the most important variables to consider in prevention programs design.